PROBLEM OF ALTRUISM MANIFESTATION AND ANTI-SOCIAL BEHAVIOUR BY YOUNG PEOPLE IN MODERN SOCIETY - Спицька, Ліана (SWorldJournal, 2023)
Under the influence of a society other people and interaction with them, specific standards of behaviour are formed and a person evaluates others with the help of those standards. But communication between members of the same group who are in the same sit